2014
DOI: 10.1007/s00421-014-2901-2
|View full text |Cite|
|
Sign up to set email alerts
|

Force–velocity relationship of leg extensors obtained from loaded and unloaded vertical jumps

Abstract: Purpose Resent research has suggested that loaded multi-joint movements could reveal a linear force-velocity (F-V) relationship. The aim of the present study was to evaluate the F-V relationship both across different types of vertical jumps and across different F and V variables. Methods Ten healthy subjects performed maximum various vertical jumps that were either loaded or unloaded by constant external forces of up to 30% of their body weight. Both the maximum and averaged F and V data were recorded. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
149
5

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 99 publications
(181 citation statements)
references
References 38 publications
27
149
5
Order By: Relevance
“…Note that the results have been obtained from either the maximum (Vandewalle et al 1987;Rahmani et al 2001;Hintzy et al 2003) or mean F and V data (Samozino et al 2012(Samozino et al , 2014aRavier et al 2004), or both (Cuk et al 2014;Sprague et al 2007). Nevertheless, note that the standard methodological approach [c.f., (Vandewalle et al 1987;Samozino et al 2012;Cuk et al 2014)] of the cited studies has been based on the manipulation of external loads providing a range of F and V data that allows for applying the linear regression model (see "Methods" for details).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Note that the results have been obtained from either the maximum (Vandewalle et al 1987;Rahmani et al 2001;Hintzy et al 2003) or mean F and V data (Samozino et al 2012(Samozino et al , 2014aRavier et al 2004), or both (Cuk et al 2014;Sprague et al 2007). Nevertheless, note that the standard methodological approach [c.f., (Vandewalle et al 1987;Samozino et al 2012;Cuk et al 2014)] of the cited studies has been based on the manipulation of external loads providing a range of F and V data that allows for applying the linear regression model (see "Methods" for details).…”
Section: Introductionmentioning
confidence: 96%
“…However, more recent studies have suggested that the F-V relationship of maximum performance multi-joint tasks could be approximately linear, such as when obtained from leg extensions where leg muscles act through closed kinetic chains (Samozino et al 2012(Samozino et al , 2014bYamauchi et al 2009), cycling (Driss and Vandewalle 2013;Nikolaidis 2012;Ravier et al 2004), vertical jumps (Cuk et al 2014;Rahmani et al 2001;Samozino et al 2014a;Sheppard et al 2008;Vandewalle et al 1987), or upper body movements (Nikolaidis 2012;van der Tillar 2004;Hintzy et al 2003;Sprague et al 2007;Cronin et al 2003). Note that the results have been obtained from either the maximum (Vandewalle et al 1987;Rahmani et al 2001;Hintzy et al 2003) or mean F and V data (Samozino et al 2012(Samozino et al , 2014aRavier et al 2004), or both (Cuk et al 2014;Sprague et al 2007). Nevertheless, note that the standard methodological approach [c.f., (Vandewalle et al 1987;Samozino et al 2012;Cuk et al 2014)] of the cited studies has been based on the manipulation of external loads providing a range of F and V data that allows for applying the linear regression model (see "Methods" for details).…”
Section: Introductionmentioning
confidence: 97%
“…While not the primary purpose of this research, the quantification of internal loads such as body mass and the contribution of work on the muscular system are also important in understanding the stresses placed on the musculoskeletal system during training. With consideration to elite lifters and near-maximal attempts, when external loading would be the dominant factor in total work performed, body weight alone can represent a proportionately large source of work for beginners, lower intensity efforts, as well as during loaded jumping exercises (Cuk, et al, 2014). While additional investigations are required to firmly describe and entrench the combined work done to overcome external and internal factors, an approximation can be made for body mass using existing models from Dempster and Gaughran (1955;1967).…”
Section: Discussionmentioning
confidence: 99%
“…For example, investigators have "simulated an increase or decrease in body weight" by attaching elastic bands to a pulley system to provide assistance to, or resistance against, an individual while performing vertical jumps [61,62]. Because the authors studied a highly dy-namic task, the inertial effects of increased body (massinduced) weight would not have been reflected by the constant external force that was applied, which may affect the interpretation of some results.…”
Section: Hypergravity and Weight Alterationsmentioning
confidence: 99%